Teachers’ Professional Practice, Policy Enactment, And Indigenous Education In Ontario: A Case Study - Currie-Patterson, Natalie (Scholarship@Western, 2019)
This qualitative case study investigates the research question: How do educators understand and enact government policies on Indigenous education in Ontario? The case study explores the content of The Ontario First Nation, Métis and Inuit Education Policy Framework, the foundational policy document for Indigenous education in Ontario released by the Ministry of Education in 2007 and a series of associated ministry publications as well as the responses of secondary school teacher participants to these policy efforts. In doing so, the case study draws on the scholarly literature about decolonizing education, as well as work on anti-colonial, anti-oppressive and critical pedagogy and employs the conceptual frameworks of policy enactment and professional knowledge landscapes to make sense of policy documents and interview data. Recruitment for the study took place in a single region of a geographically large school board in Southwestern Ontario, yielding four educators who took part in a series of three individual interviews each. Three of the four participants also took part in a final focus group interview. Interview data was considered alongside data gathered via a document analysis of Ontario Ministry of Education policy documents. Data analysis demonstrated that the Framework has proven to be largely unavailing in the day-to-day practice of teacher participants as teachers revealed a disconnect between policy content and their classroom practice. Also apparent were participant understandings of the gaps that exist between policy intent and policy action at the systemic level. Teachers saw these gaps as responsible for the non-enactment of the Framework and related policies in their daily practice. Based on the research findings, specific and actionable strategies are recommended to support the enactment of Indigenous education policy in Ontario classrooms and schools.